Storage stability study of fish soluble as a possible source of fertilizer. - Lawas, Cora Jane C. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1995)
This study aims to utilize fish soluble from fish washing as a possible source of fertilizer. Since it is highly perishable, experiments were conducted to retard or halt the onset of spoilage. Preliminary test was conducted by exposing the fish soluble at ambient temperature. Results recealed that the pure fish soluble spoiled readily after 24 hours. Further test revealed that after 48 hours, pungent odors were detected. Preservatives were added to retired spoilage. These were added to 250 ml of fish soluble samples. All of the six treatments were added with citronell oil. Treatment A is with butyl-hydro-toluene (BHT), treatment B is with alum, treatment C is with agar, treatment D is with the combination of BHT and agar, treatment E is with the combination of alum and agar and treatment F is with the combination of BHT, alum and agar. Each treatment was then pasteurized for 20 minutes at 80 Degree C. the pH and total volatile base nitrogen were used as objective tests. Whereas, the odor and color evaluation was used for sensory evaluation. Results of theses tests revealed that three formulations were stable after 15 days. These were treatment A, C and D. Since these three formulations have more or less the same utility per sample was calculated. The results showed that treatment A, cost less relative to treatment C and D. treatment A was the further analyzed for its nutrient composition. The analysis showed that it contained 9.575 nitrogen (%N), 0.32% phosphorus (P) and no amount of potassium (K). It is therefore recommended that addition of organic substances rich in phosphorous and potassium will complete the primary requirements needed by plants. Consequently, a 1.47:4:3 nitrogen-phosphorus-potassium (NPK) ratios is needed to fortify the stabilized formula.
Keywords: Fish-Processing.